Genetic variability in popcorn synthetic population (Acta Scientiarum. Agronomy, 2018)
The Brazilian popcorn has low genetic variability and the successful development of advanced lines, new popcorn cultivars with high grain yield (GY) and expansion volume (PE) is dependent on parental selection and precise determination of heterotic groups. The aim of this study was to evaluate genetic variability and identify heterotic groups in synthetic populations of popcorn, using diallel crosses. Thus, nine synthetic populations were crossed using complete diallel scheme. The GY and PE traits of 36 hybrids and reciprocals were evaluated in a randomized complete block design with 72 treatments and two replicates in two years. The effects of non-additive genes were the most important in the genetic control of these traits, indicating a favorable situation to produce hybrids. The reciprocal effect is mainly due to non-maternal effects for GY and PE. The highest GY values were obtained for the 02 x 08, 04 x 09, 05 x 09, and 01 x 09 crosses and the highest PE were obtained for the 07 x 01 and 03 x 04 crosses. The exploitation of synthetic populations from S3 lines can be an alternative to increase the genetic variability for grain yield and popping expansion in popcorn breeding programs.